The proportion hyperhomocysteinemia in chronic kidney disease patients - Pinzon, Rizaldy Taslim; Sanyasi, Rosa De Lima Renita; Pramudita, Esdras Ardi (Asian Journal of Medical Sciences, 2020)
Background: Chronic kidney disease (CKD) patients often have a high homocysteine level Hyperhomocystinemia considered as one of cardiovascular disease risk factor in CKD patients. Studies concern on the proportion of hyperhomocysteinemia in patients with CKD in Indonesia are very limited. Aims and Objectives: The main objective was to identify the proportion of hyperhomocysteinemia in CKD patients. Materials and Methods: This was a cross sectional study. Subjects in this study were CKD patients with routine hemodyalisis two times per week. Five mililiters venous blood was collected before the first hemodyalisis. The blood was stored into tubes contain clot activator. Homocysteine level higher than 15.39 μmol/L considered as hyperhomocysteine. Results: Total of 122 subjects included at this study. Subjects dominated by male with mean age of 51.7 years. Anemia (86.9%) and hypertension (86.1%) were the common comorbidities. Co-treatment assessed in this study i.e.: folic acid, calcium carbonat, antihypertensive agent, antidiabetic agent, antiplatelet agent, lipid lowering agent, and hematopoietic agent. The prevalence of hyperhomocysteinemia was high (89.3%) despite of the high consumption of folic acid in subjects (86.1%). Conclusion: Hyperhomocysteinemia is a common condition among CKD patients with hemodyalisis.